Prediction of physico-mechanical properties of rocks using dominant frequency of vibration during rotary drilling - C. R, Lakshminarayana; .Tripathi, A.K; Pal, S.K. (International Journal of Engineering and Technology, 2018)
In this study, an attempt is made to estimate some of the important physico-mechanical properties of sedimentary rocks using second-order multiple regression mathematical models. For model development, different drilling operational parameters and equivalent dominant frequencies of vibration excited at spindle head during rotary drilling were used. The prediction capacity or performance of the developed models was evaluated by using variance account for (VAF), root mean square error (RMSE) and mean absolute percentage error (MAPE).In addition, the strength of the relationship between measured and predicted value of rock properties are also checked using the Pearson correlation coefficient. Prediction performance indicators and correlation coefficients showed that the prediction model developed through the approached method can be successfully used for preliminary investigation of physico-mechanical properties of rocks which are often used as a primary data for the design of mining and civil engineering projects.